Meningkatkan Hasil Belajar Peserta Didik Kelas V pada Materi IPAS dengan menggunakan Model Pembelajaran Problem Based Learning SD Negeri 107417 Sei Merah - Aisyah Butar Butar; Dalimawatiy Kadir; Dinda Yarshal; Fitriani Fitriani; Icca Fransiska Sinaga (Journal on Education, 2024)
The low activity and learning outcomes of students in IPAS subjects are the main foundation in this study. The purpose of this study is to find out how well the application of the Problem Based Learning (PBL) learning model is in improving the learning activities and outcomes of elementary science and science. This research was conducted at SD Negeri 107417 Sei Merah. This research uses Classroom Action Research (PTK). The respondents of this study are 25 students in class V of SD Negeri 107417 Sei Merah. The data collection techniques in this study are observation and test techniques. The data collection instrument used is an observation sheet and a multiple-choice test. The results of the study showed that teacher activity in the first cycle was 66% and in the second cycle it increased to 87%. Student activity in the first cycle was 50% and in the second cycle it increased to 84%. Then the learning outcomes of students in the first cycle were 56% and in the second cycle increased to 92%. So it can be concluded in this study that the application of the Problem Based Learning (PBL) learning model can improve the activities and learning outcomes of class V of SD Negeri 107417 Sei Merah.